AUTOEVALUACION DE LA MAESTRIA EN CIENCIAS DE LA ENFERMERIA - Vega, Nora A. (2010)
This article presents the results of a self-assessment of the Master of Nursing Science, part of the Graduate Program in Nursing, School of Nursing. 5 students participated, 7 graduates, 5 teachers, 6 members of the Graduate Program Committee, 1 administrative assistant, and 8 employers (Mexico Hospital, Hospital Tony Facio Limón, Cartago Hospital, Hospital San Juan de Dios, CENARE Institute National Insurance, the School of Nursing at the University of Costa Rica and the College of Nurses). The objective was to determine the functioning of the academic expertise of Science in Nursing and the impact on the profession to develop strategies to improve the training of researchers (as) in the discipline. The implemented design is suggested by the system of Graduate Studies at the University of Costa Rica which consists of stages, components and patterns. Established three phases: 1. Awareness of the process 2. Development, validation and application of tools and techniques for data collection, 3. Processing and analysis. As a result it was observed that there were significant discordant elements in the different components (students, curriculum, graduates, employers, research, academic management, design, and political feasibility) that influence the success of the master and can be addressed from a position politics and logistics of the Graduate Program. We conclude that the construction of theoretical and methodological approach outlined in the curriculum plan is consistency and coherence between the training it offers and the academic and professional profile, however in thedevelopment of a master is internal and external factors that influence their success or failure and undermine the logic of an educational plan.